Germline Predisposition and Copy Number Alteration in Pre-stage Lung Adenocarcinomas Presenting as Ground-Glass Nodules - Ren, Yijiu; Huang, Shujun; Dai, Chenyang; Xie, Dong; Zheng, Larry; Xie, Huikang; Zheng, Hui; She, Yunlang; Zhou, Fangyu; Wang, Yue; Li, Pengpeng; Fei, Ke; et al. (Frontiers in Oncology, 2019)
Objective: Synchronous multiple ground-glass nodules (SM-GGNs) are a distinct entity of lung cancer which is emerging more and more these years in China. The oncogenesis molecular mechanisms of SM-GGNs remain elusive. Methods: We investigated single nucleotide variations (SNV), insertions and deletions (INDEL), somatic copy number variations (CNV), and germline mutations of 69 SM-GGN samples collected from 31 patients using target sequencing (TRS) and whole exome sequencing (WES). Results: In the whole cohort, many known driver mutations were found, including EGFR (21.7%), BRAF (14.5%), and KRAS (6%). However, only one out of the 31 patients had the same somatic missense or truncated events within SM-GGNs, indicating the independent origins for almost all of these SM-GGNs. Many germline mutations with low frequency in Chinese population and genes harboring both germline and somatic variations were discovered in these pre-stage GGNs. These GGNs also bore large segments of copy number gains and/or losses. The CNV segment number tended to be positively correlated with the germline mutations (r = 0.57). The CNV sizes were correlated with the somatic mutations (r = 0.55). A moderate correlation (r = 0.54) was also shown between somatic and germline mutations. Conclusion: Our data suggest that the precancerous unstable CNVs with potentially predisposing genetic backgrounds may foster the onset of driver mutations and the development of independent SM-GGNs during the local stimulation of mutagens.